(3GdfhGOQ hGdRjGQGJ Ydi eG aj GdeOhfI hZjQgG ef GdCegGJs - (3YHO Gddg Hf YHO GdQMef GdfaRi GdbjQhGfi GdeGdcj , CHh eMeO , GHf CHi RjO , J (B386 (3g`s; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3HGdKGfi ef cJGH GdLfGjGJ s
(3BNQgG (B:s
(3GdYed ai CjeGf GdbSGeI hcjajI GdMda ajgG s
(3hHBNQ gPG GdLRA dhMJGf ef Chd GdLRAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B10 - (3U (B284 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(1497) s
Keywords: (3Gdabg GdeGdcjs